(untitled) (Journal of Guidance and Counselling Studies, 2024)
This paper explores the potentials of integrity awards and badges in fostering a positive school climate in secondary schools in Nigeria. By recognizing and rewarding students’ and teachers’ integrity through awards and badges. Schools can promote a culture of honesty, respect and responsibility. This study explored how integrity awards and badges can be a catalyst for a positive school climate, examining how such awards and badges can motivate students and teachers to demonstrate integrity. The study provide insights into the effectiveness of integrity awards and badges in promoting a positive school climate in Secondary schools in Nigeria.